1998
DOI: 10.13181/mji.v7isupp1.1120
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins of <em>S. typhi</em> and their reactivity with sera from patients with Typhoid fever

Abstract: Heat shock proteins of S. typhi and their reactivity CLinicaL fertures and pathogenesis 225 CP.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Previous work in our lab documented that heat shock proteins are induced and expressed in S. enterica serovar Typhi following thermal stress (31). This led us to investigate whether there were any polymorphisms or heterogeneity within the 1.6-kb groEL gene between serovar Typhi strains.…”
Section: Discussionmentioning
confidence: 96%
“…Previous work in our lab documented that heat shock proteins are induced and expressed in S. enterica serovar Typhi following thermal stress (31). This led us to investigate whether there were any polymorphisms or heterogeneity within the 1.6-kb groEL gene between serovar Typhi strains.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, we also identified PhoN, a PhoP-regulated phosphatase, as well as heat shock proteins GroEL and DnaK, as immunoreactive. Overall, heat shock proteins are often immunogenic (32,52), and immunization of mice with purified S. Typhi GroEL induces an IgG response and confers 70 to 90% protection against lethal intraperitoneal challenge with S. Typhi and S. Typhimurium in a murine model (31).…”
Section: Discussionmentioning
confidence: 99%
“…In Salm. Typhi, heat shock treatment induced an inhibition of DnaK expression, while its basal level was very high (Tang et al 1997). A study is needed to clarify the inhibition of DnaK expression by gamma rays; however, according to Calini et al (2003) DnaK level could be a function of time and irradiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Although all the cells were killed at this radiation dose, we observed a substantial increase in the synthesis of the three Hsps proteins in E. coli and GroEL protein in the three other bacteria. This may be related to the fact that Hsps induction occurs very rapidly, and that it is detectable even after 5-10 s of exposure in a hostile environment (Tang et al 1997). Irradiator was used to deliver radiation at a dose rate of 4AE6 kGy h )1 and, therefore, the treatment lasted several minutes to reach the lethal dose.…”
Section: Discussionmentioning
confidence: 99%